Landasan ontologi, epistemologi dan aksiologis dalam kajian pendidikan karakter - Amalia Ngazimah; Darmiyati Zuchdi (Universitas Ahmad Dahlan, 2020)
This study aims to reveal the foundation of ontology, epistemology and axiology in an article entitled